Promoting college students’ systems thinking in asynchronous discussions: Encouraging students initiating questions - Yu, Yawen; Chen, Gaowei; Tao, Yang; Li, Xiaofeng; Yang, Lina; Dong, Shengwen (Frontiers in Psychology, 2022)
Systems thinking is an important skill for medical students. This study examines if encouraging students initiating questions on asynchronous discussion forum supports their systems thinking development during the COVID-19 health crisis. Twenty-two junior students participated in this study. We compared if and how students developed systems thinking when they were encouraged asking questions in asynchronous discussion forums in one unit with another unit in which traditional method was used. Students were identified with three participatory roles through social network analysis. Quantitative results showed that all students improved systems thinking compared with traditional teaching unit among which leader students improved most. Further analysis on students’ discussion posts suggested leader students asked high systems thinking level questions and provided high level responses. Epistemic network analysis unpacked how leader, regular and peripheral students engaged in initiating questions and providing responses differently. Practical implications for instructors teaching online courses were discussed.